Reformulation of the Recidivist Concept in the Juvenile Criminal Justice System in Indonesia - Rafika Nur; Handar Subhandi Bakhtiar; Prayitno Imam Santosa; Nurhayati Mardin (Jurnal Hukum Volkgeist, 2022)
Protection of children against the law is essentially an effort to protect children's rights. This study aims to provide an overview of the meaning of repeated offenders against children and efforts to realize the protection and fulfillment of children's rights in violation of the law. This research is a normative legal research with a legal and analytical perspective. The results of this study indicate that the concept of children as recidivists in juvenile justice has so far failed to provide a sense of justice for children. The criminal justice system for children is underused to protect the rights and future of children as perpetrators and victims of crime. More and more children intersect with the law and even become repeat offenders. According to the Criminal Code and the Law on the Juvenile Criminal Justice System, legal protection for children is not clearly regulated in repeated cases. According to Article 7 of the Law on the Juvenile Criminal Justice System, children who (repeatedly) commit criminal acts cannot be disturbed. According to Article 488 of the Criminal Code, the perpetrators of the second (repeated) crime are threatened with one third of the sentence.